Understanding the dimension of job resources, personal resources and transformational leadership in boosting work engagement level among employees in public sector - Zakaria, Zaki; Idris, Khairuddin; Abu Samah, Bahaman; Zainal Abiddin, Norhasni (Human Resource Management Academic Research Society, 2018)
Work engagement is the envy of many organizations. The argument is simply based on numerous benefits it offers on plate. Many studies have confirmed that work engagement has massive influence for various positive results that leads towards better performance of individual and organizations. For Malaysian public service employees, they have been identified as the primary facilitators in ensuring all government initiatives and programmes are carried out effectively. This has been outlined in the Government Transformation Programme (GTP) as Malaysia has bold intention towards becoming a fully developed nation by 2020. Thus, public servants must be fully engaged in their daily activities as this the key towards recording excellence performance as wish by citizen and stakeholder. However, several reports from multiple organizations regarding that Malaysia has recorded low percentage of having engaged workforce. This scenario needs urgent attention as disengaged employees are associated with many negative consequences such low productivity, high turnover and even drive customers away. From the public service perspective, the future of our nation building is at stake. Based on literature reviews, job resources, personal resources and transformational leadership have profound impact towards increasing level of engagement among employees. Hence, understanding on certain dimension of the aforementioned three variables above is vital as they are able to explain work engagement among public servants.